Meditation as a way of philosophical thinking and existential being - Mažeikis, Gintautas (Religija ir kultūra, 2008)
Possibilities of existential philosophical meditation are discussed in the article. The epistemological and existential experiences are analyzed and forms and limits of understanding are described there. The article discusses considerations of T. Sodeika about modes of understanding: praying, silence, evidence, inter-passivity, irony, obedience. The modes are compared with standpoints of Anselm of Canterbury, St. Bonaventura, R. Descartes, M. Buber, E. Husserl, M. Mamardaschvili, P. Wust, T. Merton were described in the texts or discussions of Sodeika. Big attention is paid to comparison reflective praxis and practices of world constitution, construction. For these reason the article contradistinguishes inter-passive, hearing meditation to the ecstatic, active, creative one. Sodeika’s ironic standpoint on the ecstatic meditation practices which were developed for example in the works of G. Bruno and G. Bataille are discussed here.